Wound Healing Properties of Jasione montana Extracts and Their Main Secondary Metabolites - Juszczak, Aleksandra Maria; Jakimiuk, Katarzyna; Czarnomysy, Robert; Strawa, Jakub Władysław; Zovko Končić, Marijana; Bielawski, Krzysztof; Tomczyk, Michał (Frontiers in Pharmacology, 2022)
The effects of different extracts obtained from Jasione montana L. (JM1–JM6) and their main metabolites on biological processes during wound healing were evaluated. The effect on wound closure in the scratch test was established, and collagen type I synthesis and anti-inflammatory effects were assessed by flow cytometry in a human dermal fibroblast model (PCS-201-012). Additionally, the antioxidant activity (DPPH and FRAP) and degree of inhibition of elastase participating in the proliferation processes of skin fibroblasts were determined in an in vitro model. The extracts and fractions were analyzed using high-performance liquid chromatography–photodiode array detection (HPLC–PDA) to quantitatively characterize their main polyphenolic compounds. The high antioxidant activity of the JM4–JM5 fractions correlated with the content of luteolin and its derivative 7-O-glucoside. Luteolin also showed the highest anti-elastase activity with an IC50 value of 39.93 ± 1.06 µg/mL, and its substantial content in the JM4 fraction presumably determines its activity (359.03 ± 1.65 µg/mL). At lower concentrations (< 50 µg/mL) of all extracts, cell proliferation and migration were significantly stimulated after 24 hours of treatment. The stimulation of cell migration was comparable with that of allantoin, which was used as a positive control. However, most of the tested extracts showed limited capacity to affect collagen type I biosynthesis. Moreover, the tested samples exhibited a complex effect on cytokine secretion, and the strongest anti-inflammatory activity through the moderation of IL-1β, IL-6 and IL-8 was observed for JM4 and luteolin. Based on the obtained results of the quantitative analysis, the anti-inflammatory activity of JM4 may be due to the high content of luteolin. In summary, extracts from J. montana, which is flavonoid-rich, promote the viability and accelerate the migration of fibroblasts as well as moderate oxidant and inflammatory processes and elastase activity. Hence, they may be potentially useful for topical therapeutic applications to stimulate the wound healing process.